Marketing Management and Tax Planning Relationships for Traditional Business Actors - Khakim, M. Azizul (ProBisnis : Jurnal Manajemen, 2024)
Traditional business actors in this era of modernization still have quite good consistency and existence. This is because people still accept and need this traditional trading system. This research is dedicated to measuring the relationship between managerial and tax planning, which can be implemented in traditional business concepts. Good managerialism can bring business into a directed and structured arrangement, while tax planning applies to assist actors in their obligations to the Republic of Indonesia. To minimize tax liabilities, various methods can be taken, both those that still comply with tax regulations (lawful) and those that violate tax regulations (unlawful), such as tax avoidance and tax evasion. Tax planning generally always starts with ascertaining whether a transaction or event has a tax impact. If the event has a tax impact, can the tax amount be excluded or reduced?.